PEMANFAATAN ENTERPRISE ARCHITECTURE PLANNING UNTUK PERENCANAAN STRATEGIS SISTEM INFORMASI STMIK DIAN CIPTA CENDIKIA KOTABUMI - Sukatmi Sukatmi (STMIK Dian Cipta Cendikia Kotabumi, 2018)
ABSTRACTSekolah Tinggi Manajemen Informatika dan Komputer Dian Cipta Cendikia (STMIK DCC) Lampung is one of college computer that is Lampung North. Until now, with all the resources that must be managed, STMIK DCC Lampung do not have processing data that integrated. Resources and data are still managed by each working unit separately with mechanism and management pattern different..To the development of information systems integrated required a plan strategy appropriate vision the mission and policy organization. By because it was necessary investigation to produce blue print of plans strategy STMIK DCC Lampung information system. This research utilizing a methodology enterprise architecture planning (EAP). The final result research is blue prints or architecture enterprise strategy of the information systems STMIK DCC Lampung. Architecture enteprise is expected to be used as the runway to build academic information system integrated at STMIK DCC Lampung. Defining enterprise it produces 8 entity, 8 information systems and 47 candidates application.